2001
DOI: 10.1523/jneurosci.21-05-01619.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hemorrhagic Stroke in a Mouse Model of Cerebral Amyloid Angiopathy

Abstract: A high risk factor for spontaneous and often fatal lobar hemorrhage is cerebral amyloid angiopathy (CAA). We now report that CAA in an amyloid precursor protein transgenic mouse model (APP23 mice) leads to a loss of vascular smooth muscle cells, aneurysmal vasodilatation, and in rare cases, vessel obliteration and severe vasculitis. This weakening of the vessel wall is followed by rupture and bleedings that range from multiple, recurrent microhemorrhages to large hematomas. Our results demonstrate that, in APP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
213
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(229 citation statements)
references
References 65 publications
(96 reference statements)
12
213
3
1
Order By: Relevance
“…We found small knob-like structures on the casted vasculature, most pronounced on microvessels like capillaries at a time point when neither parenchymal nor vascular amyloid deposits were present (20,43,44). They could form two different structures, which we described as pompons and cubes, both extruding into endothelial cells and/or neuropil and staining positive for amyloid.…”
Section: Vascular Corrosion Casting Vascular Morphology and Networkmentioning
confidence: 79%
“…We found small knob-like structures on the casted vasculature, most pronounced on microvessels like capillaries at a time point when neither parenchymal nor vascular amyloid deposits were present (20,43,44). They could form two different structures, which we described as pompons and cubes, both extruding into endothelial cells and/or neuropil and staining positive for amyloid.…”
Section: Vascular Corrosion Casting Vascular Morphology and Networkmentioning
confidence: 79%
“…In contrast, APP transgenic mice with very severe VA␤ pathology (APP23 mice) develop spontaneous cerebral hemorrhage (Winkler et al, 2001), and, similar to human CAA patients, it is likely attributable to derangement and loss of smooth muscle cells (Winkler et al, 2001) and other destructive consequences of A␤-related toxicity (Christie et al, 2001). The degree of treatment-related effects such as microhemorrhage will probably vary depending on the severity of baseline VA␤ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…9,38 No specific disease has been attributed to medin amyloid deposits. However, as it has been shown that amyloids of other biochemical nature found in the vasculature may cause a weakening of the vessel wall, [27][28][29] it is reasonable to believe that medin is deleterious to the surrounding tissue and is also involved in conditions such as thoracic aortic dissections and aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 It has been shown in a mouse model of Ab cerebral amyloid angiopathy that the amyloid deposits are associated with disorganized medial smooth muscle cells and a substantial loss of these cells. 29,30 Therefore, it is logical to believe that the sometimes widely spread medin amyloid deposits in the thoracic aorta are associated with aortic wall weakening. In this study, we have studied the prevalence of medin in aortic tissues of patients suffering from sporadic thoracic aortic dissection and aneurysm.…”
mentioning
confidence: 99%